2015
DOI: 10.1038/ejhg.2015.70
|View full text |Cite
|
Sign up to set email alerts
|

A rare variant in MCF2L identified using exclusion linkage in a pedigree with premature atherosclerosis

Abstract: Cardiovascular disease (CVD) is a major cause of death in Western societies. CVD risk is largely genetically determined. The molecular pathology is, however, not elucidated in a large number of families suffering from CVD. We applied exclusion linkage analysis and next-generation sequencing to elucidate the molecular defect underlying premature CVD in a small pedigree, comprising two generations of which six members suffered from premature CVD. A total of three variants showed co-segregation with the disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…A rare functional variant [c.2066A4G p. (Asp689Gly)] in MCF2L was detected in a small pedigree with premature CVD. The presence of the MCF2L protein was found in human atherosclerotic coronary arterial tissue compared with healthy tissue, and the variant led to impaired MCF2L-DH-domain-dependent actin stress fiber formation, indicating that MCF2L might play a role in premature atherosclerosis pathobiology ( 49 ). A genetic finding suggested that the rs4376531 of ARHGEF10 is a risk factor for atherothrombotic stroke in the Chinese Han people ( 50 ).…”
Section: The Emerging Role and Interaction Mechanisms Of Rho Gef In Atherosclerosismentioning
confidence: 99%
“…A rare functional variant [c.2066A4G p. (Asp689Gly)] in MCF2L was detected in a small pedigree with premature CVD. The presence of the MCF2L protein was found in human atherosclerotic coronary arterial tissue compared with healthy tissue, and the variant led to impaired MCF2L-DH-domain-dependent actin stress fiber formation, indicating that MCF2L might play a role in premature atherosclerosis pathobiology ( 49 ). A genetic finding suggested that the rs4376531 of ARHGEF10 is a risk factor for atherothrombotic stroke in the Chinese Han people ( 50 ).…”
Section: The Emerging Role and Interaction Mechanisms Of Rho Gef In Atherosclerosismentioning
confidence: 99%
“…In addition, GEFs can modulate a similar mechanism through Rac activation during angiogenic control in mouse tissue (Mammoto et al, 2008) (Figure 5b). Maiwald et al (2016) showed that the MCF2L-p.Leu689Gly variant, in the DH domain, was responsible for a lack of activation of Rac1 and consequently no actin stress fiber formation causing an atherosclerosis phenotype in the studied family (Maiwald et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maiwald et al (2016) showed that the MCF2L ‐p.Leu689Gly variant, in the DH domain, was responsible for a lack of activation of Rac1 and consequently no actin stress fiber formation causing an atherosclerosis phenotype in the studied family (Maiwald et al, 2016). This study showed MCF2L was abundantly expressed in atherosclerotic tissue whereas absent in healthy artery segments.…”
Section: Discussionmentioning
confidence: 99%
“…Their associations at the transcriptome level are presented in Figure 8A, which shows 2 genes with negative correlation, among which TFR2 mutation might result in abnormality in the cell cycle [24], while RALGPS1 was found to be associated with lung cancer as well as acute lymphoblastic leukemia [25]. By contrast, the remaining 2 genes showed positive correlation, among which, MCF2L could serve as the diagnostic biomarker for inflammatory response [26,27], whereas HARS could serve as the biomarker for monitoring disease progression [28]. Taken together, these results indicated that many of these genes play a vital role in cancer.…”
Section: Selecting the Feature Genes Of Melanoma And Constructing The Prognosis Modelmentioning
confidence: 99%